Moral education of younger schoolchildren by means of fiction - Shogina E. O. (Youth science in the modern world, 2025)
The article examines the role of fiction in the formation of moral qualities in younger schoolchildren. It also describes how literary works influence the development of moral values and ethical norms in children.
Keywords: воспитание; моральные ценности; education; младшие школьники; нравственные качества; moral qualities; primary school students; художественная литература; Fiction; этические нормы; moral values; ethical standards